America's hidden corners: Places off beaten path (National Geographic Society Washington, DC, 1983)
An illustrated guidebook to lesser known places in America, such as historic towns, coastal regions, remote deserts and mountain ranges. The volume details accommodation, festivals and activities that are available in each region.
Foreword; The Great Basin; The Chesapeake Bay; The Prairie and Badlands; The Upper Peninsula; The Gulf Coast; The Ozarks; The Four Corners; Notes on Contributors; Acknowledgements; Index
Includes index
Keywords: United States -- Description and travel